Welfare-improving misreported polls - Durazzo, Felipe Ricardo (2018)
We introduce an electoral pollster in a two-candidate costly voting model to study the incentives that pollsters have regarding the release of poll results. In our model, the pollster has private knowledge about the distribution of citizens\' preferences, but it may report false information to the public. If this happens, we say the pollster is misreporting the poll. An often heard criticism about pollsters is that they might manipulate in order to benefit some candidate. We show that they have incentives to misreport even in the absence of ideological motives. Moreover, misreported polls are welfare-improving relative to truthful polls.